O papel do estado brasileiro e seus reflexos em uma economia de mercado sob o enfoque do consumidor - Daniel Firmato de Almeida Gloria (2012)
This study aims to demonstrate that the social dimension of regulation is an alternative to the sustainability of a society as unequal as that of Brazil, particularly with regard to diffuse consumer interests. Based on the definition of a liquid society, this study states that the consumer is entitled to specific regulatory protection from a social dimension perspective. I The studys itinerary is outlined in the introduction by explaining the need to rethink the format of traditional ideological disputes in which a larger State means a smaller market, and gives rise to other guidelines that might organize current controversies, especially those related to the consumer market. The current situation is a perfect backdrop for the development of this work, given the belief that consecutive years of primacy of the doctrine of economic liberalism has only proven that a fully unregulated market, free from the shackles of State intervention, can neither regulate itself nor impose limits on its activities. Socialregulation is, therefore, made relevant, especially in relation to consumers noneconomic interests, which are linked to the social goals of which Social Regulation is the custodian. A straightforward language was chosen for the presentation of this thesis, without neglecting a solid theoretical foundation. An interdisciplinary method of analysis is imperative in the field of social sciences, and has led to research in theareas of Economic Law, Consumer Law, Sociology, and Regulatory Law. The concept of an economy centered on the humanism of Francois Perroux keeps a dialogic relationship with the liquid society of Zygmunt Bauman, and all of the consequences that the current condition of the market system has on humans. As a substrate, the Brazilian reality is studied based on recent data from the Human Development Report. The Brazilian economic growth, which led the country to be ranked as the world's seventh largest economy, is compared against its seventy-thirdposition in the Human Development Index (HDI), and its well-documented social stratification and its harmful consequences for the consumer market as a whole. The work is divided into three parts. It aims to recover the historical construction of the Brazilian state in light of the State and Law paradigms. Such a construction is further elaborated after identifying the processes of creation and development of its regulation. From the perspective of Brazils current consumer society, the focus is then directed to the particular field of Consumer Law. For this purpose, the existing market interaction between business, consumers, and the State is systematically delineated. Based on this connection, the need for social regulation on constitutional rights is shown. The investigation takes on a more dynamic shape, which is consistent with the plural profile of Brazilian society and in accordance with data fromthe Human Development Report. It suggests it is mandatory that sectorial regulatory activity focus on the social area for the purpose of promoting an effective rebalancing of market relations, especially in their pre-agreement phase, in which the consumer is not provided with sufficient and clear information about the products and services. Finally, the development of specific policies for social regulation is recommended.